Sengketa Hukum Pemegang Cessie yang Dibeli dari badan Penyehatan Perbankan Nasional - Nikmah Dalimunthe; Khoirun Niswah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
One way of resolving non-performing loans or better known as "bad credit" is by taking over credit through cessie. Cessie is a way of transferring and or transferring ownership rights where the object of the transfer referred to here is receivables on behalf of. In Article 613 of the Civil Code paragraph (1) it is emphasized that the transfer of receivables on behalf of must be carried out by making an authentic deed or a private deed called a Cessie deed, in which the rights to the property are transferred to a third party as the transferee. In paragraph (2) it is added that the surrender does not have legal consequences for the debtor but after it has been notified to him or in writing it is approved and acknowledged.